The documentation of cultural heritage sites in Cyprus using integrated techniques: the case study of the Church of Agios Athanasios and Kyrillos - Themistocleous, Kyriacos; Evagorou, Evagoras S.; Mettas, Christodoulos; Prodromou, Maria; Hadjimitsis, Diofantos G. (My University, 2020)
Rapid technological development, as well as the great interest in the three-dimensional (3D) digitization of cultural heritage had resulted in the research project “Ecclesiastical Cultural Heritage Digitization Pilots for the Churches of Cyprus and Crete.” The main objective is to document churches using a variety of non-invasive techniques in order to generate 3D models of the church for the management and promotion of cultural heritage sites, such as churches. In this paper, the integration of various technologies was used to document the 17th century Church of Αgios Athanasios and Kyrillos in Agios Athansios in Cyprus. Technologies such as spectroscopy, laser scanning, multispectral and RGB imaging and photogrammetry were used to obtain a high-quality 3D-metric model for documentation. The implemented techniques on the 3D-models assist in qualifying pathologies in the cultural heritage site. Through the use of spectroscopy and multispectral imaging, the authors attempt to qualify the pathologies at church using a proposed Lithology Condition Index (LCI). The methodology used in this study was developed within the framework of the EXCELSIOR project.
Keywords: Cultural Heritage; Multispectral; Spectroscopy; Lase scanner; Photogrammetry; Ecclesiastical Monuments